High Activity and Excellent Stability of Ternary Ru(CoSe2)/C with Enhanced Ru Utilization. Issue 9 (1st January 2018) - Zheng, Jiwu; Gong, Qing; Gong, Shuiping; Yang, Weifeng; Cheng, Xuan; Huang, Liuying; Li, Hengyi
Abstract : A small amount of ruthenium (Ru) was introduced into binary CoSe2 /C through chemical reduction to obtain ternary Ru(CoSe2 )/C. The effects of heat-treatment (HT) on crystal structures and electrocatalytic activities toward oxygen reduction reaction (ORR) of binary and ternary catalysts were investigated. Upon the heat-treatment at 400°C, a simple phase transformation from orthorhombic to cubic CoSe2 took place in the absence of Ru, resulting in larger crystallite size and poorer ORR activity of CoSe2 /C-HT. However, with the incorporation of Ru, a new cubic (Rux Coy )Se2 like phase might be formed as the Ru could enter the CoSe2 lattice during the phase transformation, which not only prevented the grain growth and stabilized the structure, but also provided the new efficient ORR active site. Ultimately, high activity and excellent stability were achieved for Ru(CoSe2 )/C-HT with the synergy of Ru with Co and Se, which significantly enhanced Ru utilization. The open circuit potential and maximum power density reached 0.87 V and 151 mW·cm −2 in the H2 /O2 single cell test, respectively, which were 24.3% and 242.5 times larger than those of CoSe2 /C-HT (0.70 V and 0.62 mW·cm −2 ), respectively. The normalized degradation was 2.2% after 1000 cycles during the accelerated degradation test.